Elementary electromagnetic theory. - Chirgwin, Brian H. (Brian Harvey); Plumpton, C. (Charles), 1920-; Kilmister, Clive William (Pergamon, 1973)
Elementary Electromagnetic Theory Volume 3: Maxwell's Equations and their Consequences is the third of three volumes that intend to cover electromagnetism and its potential theory. The third volume considers the implications of Maxwell's equations, such as electromagnetic radiation in simple cases, and its relation between Maxwell's equation and the Lorenz transformation. Included in this volume are chapters 11-14, which contain an in-depth discussion of the following topics: Electromagnetic Waves The Lorentz Invariance of Maxwell's Equation Radiation Motion of Charged Particles Intended.